Powerful anticonvulsant action of IL-1 receptor antagonist on intracerebral injection and astrocytic overexpression in mice - Vezzani, A. (The National Academy of Sciences, 2000)
IL-1β and its endogenous receptor antagonist (IL-1Ra) are rapidly induced by seizures in the rodent hippocampus. Exogenously applied IL-1β prolongs seizures in an IL-1R type I-mediated manner. This effect depends on N-methyl-d-aspartate receptor activation. We report here that intrahippocampal application of recombinant IL-1Ra or its selective endogenous overexpression in astrocytes under the control of glial acidic fibrillary protein promoter potently inhibits motor and electroencephalographic seizures induced by bicuculline methiodide in mice. Accordingly, transgenic mice show a reduced seizure-related c-fos mRNA expression in various forebrain areas compared with their wild-type littermates. Recombinant IL-1Ra was ineffective in mice deficient in IL-1R type I, having per se a delayed onset to generalized convulsions. These results demonstrate that IL-1Ra mediates potent anticonvulsant effects acting on IL-1R type I and suggest that the balance between brain IL-1β and IL-1Ra represents a crucial mechanism to control seizure generalization.